Understanding the Perception of Bangladeshi SMEs towards Marketing of Financial Products (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Literature depicts Small and Medium Enterprises  (SMEs) play a dominating role in improving  the economic status of a country, especially in  developing countries. However, access to credit  is a major problem which SMEs face worldwide.  The problem of financing is dealt by offering of  different financial products like bank loan, line  of credit by the banks to the SMEs. As marketing  communicates the potential clients about the  products and services, it is crucial to understand  SMEs viewpoint towards marketing financial  products. Hence, the present study attempts  to capture the perspectives (i.e., benefits and  associated risks) of people associated with SMEs  and SMEs’ owners towards the marketing of  financial products in a developing country like  Bangladesh.
Keywords: Bangladesh; SME; Financial; Product; Credit